Emerging Biomarkers for the Diagnosis and Monitoring of Inflammatory Bowel Diseases. Issue 8 (August 2016) - Soubières, Anet A.; Poullis, Andrew
Abstract : Abstract: There is currently no single test available to confidently diagnose cases of inflammatory bowel disease (IBD). Physicians rely on a number of diagnostic tools, including clinical evaluation, serum testing, and imaging, which are used on conjunction with endoscopic evaluation. It is often difficult to determine whether patients with abdominal pain and change in bowel habit have functional bowel symptoms or whether they have a true diagnosis of IBD. Even once a diagnosis of IBD has been made, a significant proportion of patients are labeled with the term "indeterminate colitis" where histological sampling cannot confidently subclassify patients as either Crohn's or ulcerative colitis. Colonoscopy is an inconvenient and uncomfortable test for most patients. In addition, it is not without serious risks of perforation, as well as risks which can be associated with sedation and analgesia given during the procedure. The use of biomarkers to aid in the diagnosis, subclassification, and monitoring of IBD is an ever expanding area. In this review, we have concentrated on noninvasive biomarkers of IBD, because these are more acceptable to patients and easier to perform in everyday clinical practice. We will first touch on those biomarkers currently well established and in wide clinical use, such as C-reactive protein, erythrocyte sedimentation rate. Faecal calprotectin and their use in the diagnosis of IBD. Following on, we will review more novel biomarkers and their use in subclassification and monitoring of IBD, including a variety of antibodies, genetics, and microRNAs, as well as touching on metabolomics.